PENGARUH KEPERCAYAAN DAN PENGHARGAAN TERHADAP KOMITMEN ORGANISASI KARYAWAN TRIBUN JAKARTA PUSAT - Iin Asikin (UNIVERSITAS INDRAPRASTA PGRI, 2015)
This study was to obtain an answer empirically the effect (1) the trust to organizational commitment partially, (2) the reward to organizational commitment partially, and (3) the trust and reward on organizational commitment simultaneously. This research was conducted at TRIBUN Centre of Jakarta, with 66 employee as respondents.The method used was a survey with multiple linear regression analysis approach. Based on the research an calculations SPSS obatained the following results : (1 )There is the effect of trust to organizational commitment partially, (2) There is the effect of reward to organizational commitment partially, and (3) There are the effect of the trust and reward on organizational commitment simultaneously.Therefore, it could be concluded that the increasing or decreasing of organizational commitment effected directly by trust and reward. This conclucion implies that when we want to improve the organizational commitment, we have to take on to consideration those two variables, trust and reward as well.